Optimization of Cargo Collection and Delivery Processes - Ulugbek Kubayev (Research Parks Publishing LLC, 2023)
issues of optimizing the processes of cargo collection and delivery are considered both regionally and internationally. A direct proportional relationship has been determined between orders for the transportation of large cargo and requests for the transportation of small cargo. It is shown that consolidation/disconsolidation of cargo can occur both at local TLCs (district, city or region level), and at regional TLCs and international TLCs (transport and logistics centers between which the main international transportation is carried out).